Fungi as Bioremediators - Goltapeh, Ebrahim Mohammadi; Danesh, Younes Rezaee; Varma, Ajit.; SpringerLink (Online service) (Berlin, Heidelberg : Springer Berlin Heidelberg : Imprint: Springer, 2013)
Biological remediation methods have been successfully used to treat polluted soils. While bacteria have produced good results in bioremediation for quite some time now, the use of fungi to decontaminate soils has only recently been established. This volume of Soil Biology discusses the potentials of filamentous fungi in bioremediation. Fungi suitable for degradation, as well as genetically modified organisms, their biochemistry, enzymology, and practical applications are described. Chapters include topics such as pesticide removal, fungal wood decay processes, remediation of soils contaminated with heavy and radioactive metals, of paper and cardboard industrial wastes, and of petroleum pollutants.
Ecophysiology of Fungal Bioremediation -- Application of Mycoremediation Against Organic Pollutants -- Mycoremediation of Inorganic Pollutants -- Mycoremediation: Agricultural and Forest Ecosystem Sustainability -- Techniques in Mycoremediation.
Keywords: Life sciences; Microbiology; Soil conservation; Biotechnology; Life Sciences; Eukaryotic Microbiology; Soil Science & Conservation; Environmental Engineering/Biotechnology.